Year-round growth potential and moisture stress tolerance of buckwheat (Fagopyrum esculentum L.) under fragile hill ecosystems of the Eastern Himalayas (India) - Rangappa, Krishnappa; Rajkhowa, Dipjyoti; Layek, Jayanta; Das, Anup; Saikia, Uday Sankar; Mahanta, Kaberi; Sarma, Anjan Kumar; Moirangthem, Prabha; Mishra, Vinay Kumar; Deshmukh, Nishant Anandrao; Rajbonshi, Namrata; Kandpal, Basant K. (Frontiers in Sustainable Food Systems, 2023)
Introduction Under a changing climate, the fragile ecosystems of the Eastern Himalayas (EH) are persistently challenged by prolonged dry spells and erratic rainfall. Identification of suitable high-yielding crops with higher moisture stress tolerance and adaptability is paramount for the region. Although the region received a good amount of rainfall in the rainy season, the winter months, viz., November to March, rarely received any rain. Even within the rainy season, there are several intermittent drought spells that hinder crop productivity. Methods The present study has used field and microcosm experiments to assess the year-round cultivation potential and extent of moisture stress tolerance in the lesser-known buckwheat crop of the region. Results and discussion Sowing of buckwheat from mid-September to mid-December produced better grain yield, the highest being when sowing in October (9.83 q ha−1) and the crop was found suitable to grow all through the year for higher green biomass (12.6–38.4 q ha−1). The moisture stress tolerance of buckwheat was significantly enhanced by increased total root length and root surface area by 12.4 and 34.7%, respectively. Increased photo-protective carotenoids, chlorophyll b, and favorable stomatal attributes with substantial epicuticular wax have significantly improved the moisture stress tolerance of Buckwheat. In addition, leaf proline was found 25.4% higher and total soluble protein, reducing sugar, and cell membrane stability were found 29.2, 38.1, and 36.5% lower compared to the control, respectively. A significantly lower rate of water loss (25.6%) with its stomatal and non-stomatal adaptations and versatile pollen structural traits under moisture stress over control, make the buckwheat crop potentially more stress tolerant and economical crop for EH of India.